Effect of the housing system (free-range vs. open air cages) on growth performance, carcass and meat quality and antioxidant capacity of rabbits. (November 2018) - Loponte, Rosa; Secci, Giulia; Mancini, Simone; Bovera, Fulvia; Panettieri, Valentina; Nizza, Antonino; Di Meo, Carmelo; Piccolo, Giovanni; Parisi, Giuliana
Abstract: Growth performances and meat quality of free-range or cage raised rabbits were compared in 36 male animals. Rabbits were raised in free-range areas (2000 cm 2 /head) or in open-air cages (800 cm 2 /head) from weaning to 99 days old. Daily weight gain and final live weight were higher (P < 0.05) for the rabbits raised in cages which presented a more favourable feed conversion ratio (P < 0.05) than in the free-range group. The average feed intake, liver and empty gastro-intestinal tract weights were higher (P < 0.05) in the free-range group, while the interscapular fat percentage was higher (P < 0.05) in the caged rabbits. Loins of free-range rabbits had higher amount of PUFA n-6 in neutral lipids (P < 0.05) whereas their polar lipids were richer in PUFA n-6 and n-3 than in those of the cage group. Muscular fat of free-raised rabbits was found to be less susceptible to be oxidized, having a higher antioxidant capacity than the caged group. Highlights: Free-range and open-air cage raising systems for rabbit were compared. Higher space availability alone was responsible of some modification in meat. Free-range raised rabbits have a higher amount of PUFA n6 in neutral lipids. Free-range raised rabbits have a higher amount of PUFA n6 and n3 in polar lipids. Meat of free-range raised rabbits had a higher antioxidant capacity.